A Performance Comparison Between Buck-Boost Based Active Cell Balancing in Pairs and Passive Cell Balancing in Lithium-Ion Batteries Application - Chow, Brendan Dennis; Poniran, Asmarashid (Evolution in Electrical and Electronic Engineering, 2023)
In designing a battery management system for lithium-ion batteries, the passive cell balancing method is more widely used compared to the active cell balancing method due to lower cost. The aim of this study is to determine the performance difference in terms of energy efficiency and balancing time between both passive and active cell balancing. The switching shunt resistor passive cell balancing and buck-boost active cell balancing in pairs are simulated and compared. The buck-boost active cell balancing uses an inductor as an energy transfer medium between cell-to-cell charging. The active cell balancing method proved to retain 3.93% SOC or 314.4 mAh more than the passive cell balancing method. Hence, the active cell balancing method is more superior and should be considered to increase lithium-ion battery lifespan in the long term.